1996
DOI: 10.1073/pnas.93.11.5539
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporters are markedly reduced in Lesch-Nyhan disease in vivo.

Abstract: Dopamine (DA) deficiency has been implicated in Lesch-Nyhan disease (LND), a genetic disorder that is characterized by hyperuricemia, choreoathetosis, dystonia, and compulsive self-injury. To Several neurodevelopmental disorders are thought to involve the neuropathology of the basal ganglia. Among them, the best known are Lesch-Nyhan disease (LND) and Rett syndrome. In both of these conditions, there is evidence for the dysfunction of the dopaminergic neurotransmission.LND is an X-chromosome-linked disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
1
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(120 citation statements)
references
References 32 publications
5
111
1
3
Order By: Relevance
“…These patients respond dramatically to treatment with low doses of the dopamine precursor L-DOPA. Another inherited disease in which dystonia is possibly due to a disturbance of dopamine synthesis is Lesch-Nyhan disease (Ernst et al, 1996;Wong et al, 1996;Visser et al, 2004), a condition in which a defect in purine synthesis gives rise to numerous medical problems, as well as neurologic symptoms including dystonia. Positronemission tomography (PET) studies in Lesch-Nyhan disease show reductions in [ 18 F]-DOPA uptake, and in labeling with WIN-35,428, a marker of dopamine transporter, in the basal ganglia and other regions of the brain (Ernst et al, 1996;Wong et al, 1996).…”
Section: The Role Of Dopamine In Dystoniamentioning
confidence: 99%
See 2 more Smart Citations
“…These patients respond dramatically to treatment with low doses of the dopamine precursor L-DOPA. Another inherited disease in which dystonia is possibly due to a disturbance of dopamine synthesis is Lesch-Nyhan disease (Ernst et al, 1996;Wong et al, 1996;Visser et al, 2004), a condition in which a defect in purine synthesis gives rise to numerous medical problems, as well as neurologic symptoms including dystonia. Positronemission tomography (PET) studies in Lesch-Nyhan disease show reductions in [ 18 F]-DOPA uptake, and in labeling with WIN-35,428, a marker of dopamine transporter, in the basal ganglia and other regions of the brain (Ernst et al, 1996;Wong et al, 1996).…”
Section: The Role Of Dopamine In Dystoniamentioning
confidence: 99%
“…Another inherited disease in which dystonia is possibly due to a disturbance of dopamine synthesis is Lesch-Nyhan disease (Ernst et al, 1996;Wong et al, 1996;Visser et al, 2004), a condition in which a defect in purine synthesis gives rise to numerous medical problems, as well as neurologic symptoms including dystonia. Positronemission tomography (PET) studies in Lesch-Nyhan disease show reductions in [ 18 F]-DOPA uptake, and in labeling with WIN-35,428, a marker of dopamine transporter, in the basal ganglia and other regions of the brain (Ernst et al, 1996;Wong et al, 1996). Mutations in the gene that codes for the rate-limiting enzyme in dopamine metabolism, tyrosine hydroxylase, also give rise to dystonias (Knappskog et al, 1995), as do mutations within the dopamine D2 receptor gene (myoclonus-dystonia, DYT11, Klein et al, 1999), or polymorphisms within the dopamine D5 receptor gene (Placzek et al, 2001).…”
Section: The Role Of Dopamine In Dystoniamentioning
confidence: 99%
See 1 more Smart Citation
“…DAT protein levels vary in normal subjects, particularly as a function of age, and deviate from the normal range in pathological states. [4][5][6][7][8] DAT protein is markedly reduced in Parkinson's disease, 9,10 Lesch-Nyhan syndrome 11 and reportedly is elevated in attention deficit hyperactivity disorder (ADHD), [12][13][14] Tourette's syndrome, 15 and major depression. 16 Chronic use of stimulant drugs such as cocaine leads to increases in DAT levels during withdrawal whereas methamphetamine results in DAT depletion, possibly a consequence of neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In epileptic foci, also, hypometabolism is larger than a mere atrophy effect [67]. Assessment of the dopaminergic system with PET has shown that dopamine transporters are noticeably reduced in Lesh-Nyhan disease; PVC highlights this finding [68]. Dopa-decarboxylase activity has been shown to be reduced greatly in patients who have Parkinson disease, compared with normal controls [69].…”
Section: Clinical and Research Applications Of Partial Volume Correctionmentioning
confidence: 99%